2019
DOI: 10.9734/jammr/2018/v28i1130038
|View full text |Cite
|
Sign up to set email alerts
|

Burden of Cancer in Plateau State, Central Nigeria: A 27-Year Report from a Tertiary Hospital-Based Cancer Registry

Abstract: Cancer has become an emerging disease in the developing world owing to the control of infectious agents and increase longevity. The global anatomical distribution of cancer differs from developed to developing (or resource limited) countries. This article provides information on hospital based cancer registry in Jos University Teaching Hospital (JUTH), for the past 27 years. This was a descriptive retrospective study of consecutive cases of cancer analyzed at the Histopathology Department of JUTH, Jos, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 29 publications
2
6
0
Order By: Relevance
“…Similarly, in an earlier report from the Benin Cancer Registry, located in the South Senatorial District of this state (not covered by the current study), Obaseki et al found a ratio of 1:1.5 [16]. This high preponderance of cancers in females seen in this state is consistent with findings from many states in Nigeria [8,13,[17][18][19][20][21]. The bias for the female gender can be attributed to high proportion of female breast cancer and cervical cancer among the common cancer types seen in the country.…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, in an earlier report from the Benin Cancer Registry, located in the South Senatorial District of this state (not covered by the current study), Obaseki et al found a ratio of 1:1.5 [16]. This high preponderance of cancers in females seen in this state is consistent with findings from many states in Nigeria [8,13,[17][18][19][20][21]. The bias for the female gender can be attributed to high proportion of female breast cancer and cervical cancer among the common cancer types seen in the country.…”
Section: Discussionsupporting
confidence: 90%
“…This was also observed in other parts of the country, namely Akwa Ibom (males-59.63;females 45.69); [5] Sokoto (males-45.77;females-43.18); [8] Abuja (Males-49.1; females-45.4); [18] and Ibadan (males-51.1; females-49.1) [18]. This may be attributed to effect of reproductive hormones which tend to influence rapid cellular proliferation and oncogenic potential at a relatively younger age [19].…”
Section: Resultsmentioning
confidence: 99%
“…The ten favored sites for cancer in descending order in this study (excluding metastatic diseases) are breast, colon and rectum, prostate, cervix, skin, ovary, stomach, lymphoid organs, thyroid and salivary gland. In some European countries and United State of America, the most common cancer in both genders is lung, breast, prostate, colorectum and urinary bladder while in West Asia and North Africa, the lung, breast, colorectum, urinary bladder, and stomach topped the list [19]. In Nigerian studies, the heterogeneity in cancer incidence is very marked although there is general agreement that prostate cancer is the most 13.7%, 14.6%, and 22.4% reported in Kano [5], Jos [6] and Akwa Ibom [7] respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies had been carried out on the natural radiation background of Nigeria, and these investigations are as a result of public outcry against radiation in the environment and increase the rate of cancer. A study recorded a total of 6,915 cancer cases within the year1987-2014 comprising of 2891 males and 4024 females in Plateau state [9], giving an annual prevalence of 256 cases per annum. The most frequent cancers were those of breast, cervical, prostate, lymphoma, and liver cancers.…”
Section: Natural Radioactive Deposit In Nigeriamentioning
confidence: 99%